Adaptive features of in vitro-derived plantlets of MD2 pineapple during acclimatization process - Hamid, Nur Syazwani (Horticultural Society of India, 2020)
Tissue culture-derived planting materials require optimal acclimatization period to ensure high survival rates in the nursery and to save labor and production cost. However, there is little information on how the morphology and physiology of in vitro-derived plantlets can be affected by culture conditions and acclimatization. We compared different types of media for shoot multiplication using thirty pineapple suckers as explants. Morphological and physiological changes of thirty field-grown plants and in vitro-derived plantlets during ex vitro acclimatization at 0, 14, 28, 42, 56 and 84 days were evaluated. Experiments were conducted in triplicate. Observations were based on the leaf morphology (number, width, ratio value of dry weight to fresh weight and succulence index of the leaves) and physiological characteristics (photosynthetic rate, stomatal conductance, transpiration rate, stomata opening, trichomes and histological examination). We found that the in vitro plantlets undergoing acclimatization showed C3 characteristics and adapted to CAM characteristics after 42 days of acclimatization. The in vitro plantlets were compared with field-grown plants and observations were made based on the morphological and physiological characteristics of the leaves. In conclusion, our findings indicated that in vitro-derived pineapple plantlets started to develop and achieve similar characteristics with the field-grown CAM plants after 42 days of acclimatization, suggesting that this could be the suitable period prior to transfer into the fields.